1997
DOI: 10.1021/jp971717k
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Persistence Length of Polymers by MD Simulations on Small Fragments in Solution. Application to Cellulose

Abstract: A procedure is described to estimate the persistence length and related properties of a persistent polymer by MD simulations of a small fragment, including solvent effects. The procedure is applied to cellulose in aqueous solution, which leads to an upper limit of the persistence length of 145 ± 10 Å. The occurrence of small amounts of folded conformations seems to be indicated by comparison of the theoretical with experimental data. The behavior of the cellulose chain is consistent with the Kratky−Porod worml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
62
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 31 publications
(36 reference statements)
9
62
0
Order By: Relevance
“…Cyclic monosaccharides can appear indeed as puckered rings, and their conformational transitions dramatically alter the equilibrium properties of both single sugar rings as well as those in oligo and polysaccharides 32 . Despite the large number of possible puckered conformers, many biologically relevant monosaccharides in the pyranoid form appear almost always in one stable puckered conformation, the second most populated state being so unlikely not to be detectable by actual experimental techniques.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cyclic monosaccharides can appear indeed as puckered rings, and their conformational transitions dramatically alter the equilibrium properties of both single sugar rings as well as those in oligo and polysaccharides 32 . Despite the large number of possible puckered conformers, many biologically relevant monosaccharides in the pyranoid form appear almost always in one stable puckered conformation, the second most populated state being so unlikely not to be detectable by actual experimental techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the large number of possible puckered conformers, many biologically relevant monosaccharides in the pyranoid form appear almost always in one stable puckered conformation, the second most populated state being so unlikely not to be detectable by actual experimental techniques. In spite of that, several authors reported an inappropriately high percentage of secondary puckered conformations [32][33][34][35][36][37] when modeling carbohydrates using classical force fields such as gromos 34,35,[38][39][40][41] or opls-aa 42 for simulations of sugars in solution. Regarding the latest gromos parameter set for carbohydrates (45a4) 35 , non-chair conformers have been shown to be accessible during equilibrium simulation runs of β-d-glucose% 28 , and two recent works 43,44 estimated the free energy difference between chair conformers to be at least 10 kJ/mol lower than most theoretical and ab-initio simulation results.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, deviations from the preferred pyranose ring conformation have been observed for non-reducing end pyranose rings in single-molecule atomic force microscopic studies of dextran [52], MD simulations of cellulose [53] and X-ray crystallographic studies of b-cyclodextrin [54], abrin [55] and neuraminidase± sialic acid complex [56].…”
Section: Pyranose Ring Conformationmentioning
confidence: 99%
“…The force field incorporating the two former modifications is referred to as the 45A3 force field. 37,38 However, simple tests using the GROMOS carbohydrate force field, either based on the original 43A1 parameter set 31,32,42,43 or on the 45A3 parameter set (unpublished data), have shown a strong underestimation of the anomeric effect and incorrect dihedral-angle distributions in simple di-and oligosaccharides, sometimes including distorted ring conformations. The required refinement of the GRO-MOS force field (mainly charges and torsional interaction parameters) in the context of hexopyranose-based carbohydrates is the goal of the present work.…”
Section: Introductionmentioning
confidence: 99%